LOGARITHM RULES -- PROOFS AND EXPLANATIONS OF FORMULAS, LINKS FOR FURTHER STUDY

Your Ad Here

Proofs and Explanations for Logarithm Formulas :

Please go to

The Proofs and Explanations for
the first five Logarithm Rules (Formulas)


and study them before the Proofs
and Explanations for the next five
Formulas, which are dealt with here.

















Proof and Explanation of Formula 6 :
Logarithm Rules

Logarithm of a Quotient:

loga (mn) = loga m - loga n

Proof:
Let loga m = P ⇒ aP = m ............(i)
Let loga n = Q ⇒ aQ = n .............(ii)
You might have observed that Equations (i) and (ii) are obtained by changing the Logarithmic form to Exponential form.
(i) ÷ (ii) gives aPaQ = mn
aP - Q = mn ( Since aPaQ = aP - Q From laws of Exponents)
⇒ loga (mn) = P - Q ( by changing Exponential form to Logarithmic form)
By Replacing the values of P and Q, we get
loga (mn) = loga m - loga n (Proved.)
In proving this, see how we made use of changing Logarithmic to Exponential form andExponential to Logarithmic form.
Remember that Logarithm of a Fraction is the difference of the Logarithms oftheNumerator and Denominator.
Remember that the Formula is not for log(m - n) nor forlog m⁄log n.
We have Formula for log(mn) and log m - log n.
We should be able to apply the formula from L.H.S. to R.H.S. and from R.H.S. to L.H.S.

Great deals on School & Homeschool Curriculum Books and Software

Proof and Explanation of Formula 7 :
Logarithm Rules

Logarithm of a Power: Logarithm Rules

loga (mn) = n loga m

Proof:
Let loga (mn) = P ⇒ aP = mn........(i)Let loga m = Q ⇒ aQ = m.............(ii)You might have observed that Equations (i) and (ii) are obtained by changing the Logarithmic form to Exponential form.
Using the value of m from (ii) in (i), we get
aP = (aQ)n
= anQ [Since (aQ)n = anQ from Laws of Exponents]
Since the Bases are equal, the Exponents have to be equal.
∴ P = nQ
By Replacing the values of P and Q, we get
loga (mn) = n loga m (Proved.)
Remember that the Logarithm of a Power is equal to the Exponent times the Logarithm of the base of the Power.
Depending on the need of the problem, you should be able toapply the formula from L.H.S. to R.H.S. and from R.H.S. to L.H.S.





Get The Best Grades With the Least Amount of Effort

Here is a collection of proven tips,
tools and techniques to turn you into
a super-achiever - even if you've never
thought of yourself as a "gifted" student.

The secrets will help you absorb, digest
and remember large chunks of information
quickly and easily so you get the best grades
with the least amount of effort.

If you apply what you read from the above
collection, you can achieve best grades without
giving up your fun, such as TV, surfing the net,
playing video games or going out with friends!

Know more about the

Speed Study System.















Proof and Explanation of Formula 8 :
Logarithm Rules

Change of Base of a Logarithm: Logarithm Rules

loga b = (logk b)⁄(logk a)

Proof:
Let logk b = P ⇒ kP = b.......(i)
Let logk a = Q ⇒ kQ = ak = a(1⁄Q).......(ii)
Substituting the value of k from (ii) in (i), we get
{a(1⁄Q)}P = ba{(1⁄Q) x P} = b
a(P⁄Q) = b ⇒ P⁄Q = loga b
Substituting the values of P and Q, we get
(logk b)⁄(logk a) = loga b
⇒ loga b = (logk b)⁄(logk a) (Proved.)
While remembering the formula, forget about k. Any variable can take its place.
This Formula is very useful in solving many a problem.
If we cross multiply the fomula, we get
loga b x logk a = logk b
In this form also, we use this Formula for change of the Base.

Great Deals on School & Homeschool Curriculum Books

Proof and Explanation of Formula 9 :
Logarithm Rules

Logarithm of a Power to the Base of another Power:

log(an) (bm) = (mn) loga b

Proof:
L.H.S. = log(an) (bm)
Applying Formula 8, we get
L.H.S. = {logk (bm)}⁄{logk (an)}
Applying Formula 7, we get
L.H.S. = {m (logk b)}⁄{n (logk a)}
= (mn)(logk b)⁄(logk a)
Applying Formula 8 again, we get
L.H.S. = (mn) loga b = R.H.S. (Proved.)
As you can see, this formula is a combination of Formulas 7 and 8.
If you remember this formula, it will help you in solving some problems.

Proof and Explanation of Formula 10 :
Logarithm Rules

Logarithm of b to the base a; b and a interchanged:

loga b = 1⁄(logb a)

Proof:
This formula is a special case of Formula 8.
We know, in formula 8, k can be replaced by any variable.
If we replace k by b in Formula 8, we get
loga b = (logb b)⁄(logb a)
Numerator of R.H.S.= (logb b) = 1 (See Formula 4)
∴ loga b = 1⁄(logb a) (Proved.)
Remembering this Formula also will help you in solving some problems.















Solved Examples : Logarithm Rules

The following Link takes you
to the set of Solved Examples.

Set of Solved Examples

Progressive Learning of Math : Logarithm Rules

Recently, I have found a series of math curricula
(Both Hard Copy and Digital Copy) developed by a Lady Teacher
who taught everyone from Pre-K students to doctoral students
and who is a Ph.D. in Mathematics Education.

This series is very different and advantageous
over many of the traditional books available.
These give students tools that other books do not.
Other books just give practice.
These teach students “tricks” and new ways to think.

These build a student’s new knowledge of concepts
from their existing knowledge.
These provide many pages of practice that gradually
increases in difficulty and provide constant review.

These also provide teachers and parents with lessons
on how to work with the child on the concepts.

The series is low to reasonably priced and include

Elementary Math curriculum

and

Algebra Curriculum.